ANALISIS KAPASITAS DUKUNG SPUN PILE PADA PILE SLAB - Kevin Fauzan, Muhammad; Yelvi, Yelvi; Wirastana Adinegara, Aldo; Sudardja, Handi (Politeknik Negeri Jakarta, 2024)
The project seeks to promote the National Economic Development (PEN), specifically targeting the enhancement and advancement of economic activities on Sumatra Island. One of the current projects is the construction of the Sicincin - Padang Toll Road Section (STA 0+000 - 36+600) of the Pekanbaru - Padang Toll Road. This segment of the highway is a component of the Trans Sumatra highway network on Sumatra Island. The bearing capacity and settlement design of the spun pile foundation at the pile slab STA 7+443 - STA 7+569 Sicincin - Padang Toll Road were recalculated based on soil investigation data derived from SPT (Standard Penetration Test) results, subsequently compared with the findings from the PDA Test (Pile Driving Analyzer) conducted in the field. Soft soil issues were identified at STA 7 + 443, leading to the formation of fissures and landslides. The issues arose from the interaction between a pile foundation plate and the capacity of a revolving pile foundation. The objective of the study is to determine the bearing capacity and settlement of the rotating pile foundation at STA 7 + 443 - STA 7 + 569 using Standard Penetration Test (SPT) results and to compare these findings with the field data obtained from the Pile Driving Analyzer (PDA) test. The analysis conducted involved the adjustment of the N-SPT value utilizing tables and graphs in compliance with SNI 1725-2016, SNI 8460-2017, and SNI 4153-2008. The settlement assessment reveals the most significant discrepancy in the Meyerhoff Method compared to the PDA Test, amounting to 5.32%. The pile's settlement is within the allowable limit of 60 mm; hence it is deemed safe.